Implementasi Branding Dan Digital Marketing Untuk Strategi Pemasaran UMKM Di Desa Ngampungan - Retno Dwi Astutik; Nurul Aulia Dewi; Aptania Fairuz Wardani; Amilia Eka Putri; Daffa Samdya Adabi Selay; Mu’tasim Billah (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
Digital marketing is a form of marketing strategy that uses the internet as a link between businesses and consumers. By using the internet, businesses can reach more consumers and expand their market share. The application of digital marketing can increase the level of customer loyalty because the consumer's sense of satisfaction to buy, identify, know the value of goods without leaving the house is fulfilled. This paper was created to describe the implementation of branding and digital marketing that the author has done as a form of community service in the Real Work Lecture program in Ngampungan Village, Bareng District. The research method used in scientific writing is descriptive by describing the activities that have been carried out and their outputs. The author provides assistance to respondents in several aspects, such as socialization regarding branding, making packaging labels, and socializing marketing on several social media platforms.